PERBANDINGAN ALGORITMA MINIMAX DENGAN ALPHABETA PRUNING PADA PERMAINAN TRADISIONAL DADOS-DADOSAN - Miftahul Qiki Winata; Muhammad Jauharul Fuadi; Aji Prasetya Wibawa (SENTIA 2016, 2016)
Minimax algorithm is well used to resolve any searching problem with a small number of possibilities. But for a larger number of possibilities, this algorithm need optimization, one of the Minimax algorithm optimization is Alphabeta Pruning. This study is purposed to compare the efficiency of the Alphabeta Pruning algorithm and Minimax algorithm through some scenario testing. The efficiency of the algorithms in terms of speed of time and number of nodes visited. The result of the testing scenario was Alphabeta Pruning algorithm can save time greater than 50% compared with the Minimax algorithm in depth of six. From the data obtained, it was concluded that: (1) Minimax and Alphabeta Pruning algorithm can be applied to Dados-dadosan game, (2) Alphabeta Pruning algorithm is more efficient than the Minimax algorithm on the Dados-dadosan game.